Similarity and variability of blocked weather-regime dynamics in the Atlantic–European region ... - Teubler, Franziska; Riemer, Michael; Polster, Christopher; Grams, Christian M.; Hauser, Seraphine; Wirth, Volkmar (Copernicus Publications, 2023)
Weather regimes govern an important part of the sub-seasonal variability of the mid-latitude circulation. Due to their role in weather extremes and atmospheric predictability, regimes that feature a blocking anticyclone are of particular interest. This study investigates the dynamics of these “blocked” regimes in the North Atlantic–European region from a year-round perspective. For a comprehensive diagnostic, wave activity concepts and a piecewise potential vorticity (PV) tendency framework are combined. The latter essentially quantifies the well-established PV perspective of mid-latitude dynamics. The four blocked regimes (namely Atlantic ridge, European blocking, Scandinavian blocking, and Greenland blocking) during the 1979–2021 period of ERA5 reanalysis are considered. Wave activity characteristics exhibit distinct differences between blocked regimes. After regime onset, Greenland blocking is associated with a suppression of wave activity flux, whereas Atlantic ridge and European blocking are associated ...